Sistem Pendukung Keputusan Penentuan Siswa Penerima Beasiswa Menggunakan Metode Topsis - Hylenarti Hertyana - STMIK Nusa Mandiri; Elly Mufida - UBSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2020)
Abstract - Determining students who are entitled to receive scholarships is not easy, therefore the assessment must be based on criteria set by the school. Often in the determination of students who are entitled to receive scholarships is constrained only by the assessment of achievement without regard to several other criteria by taking into account the financial ability of the student's family and various other determinants. This Decision Support System uses the Technique for Others Preference by Similarity to Ideal Solution (TOPSIS) method. The type of data used in this study is primary data. Primary data was obtained by the writer from one of the private schools through direct observation and direct interviews in the student section, especially in the process of receiving school scholarships. This study aims to develop the application SPK (Decision Support System) in determining students who are entitled to receive scholarships. Based on the results of observations and interviews obtained 5 criteria including Parent Income (K1) obtained from monthly income, Number of Dependents (K2) obtained from the number of dependents in the family, Residence Status (K3) obtained from the Status of Residence Ownership, School Achievement (K4) ) is obtained from the Ranking Ranking in school, Achievement outside of School (K5) is obtained from Achievement outside of school. While secondary data obtained through scientific writing and literature studies that the authors do based on the writing theme. The results of this study produce outputs that meet the objectives and facilitate the process of determining students who are entitled to receive scholarships, so that they become more accurate, effective and efficient in producing information that can be used as decision support.Keywords: Decision Support System, Scholarship, TOPSIS Method. Abstrak – Menentukan siswa yang berhak menerima beasiswa bukanlah hal yang mudah, oleh karena itu penilaian tersebut harus didasarkan pada kriteria yang sudah ditetapkan oleh sekolah. Sering kali didalam penentuan siswa yang berhak menerima beasiswa terkendala pada hanya penilaian pada prestasi saja tanpa memperhatikan beberapa kriteria lainnya dengan memperhatikan kemampuan finansial keluarga siswa tersebut dan berbagai faktor penentu lainnya. Sistem Pendukung Keputusan ini menggunakan metode Technique for Others Preference by Similarity to Ideal Solution (TOPSIS). Jenis data yang digunakan dalam penelitian ini adalah data primer. Data primer diperoleh penulis dari salah satu sekolah swasta melalui observasi langsung dan wawancara secara langsung pada bagian kesiswaan khususnya pada proses penerimaan beasiswa sekolah. Penelitian ini bertujuan mengembangkan aplikasi SPK (Sistem Pendukung Keputusan) didalam menentukan siswa yang berhak menerima beasiswa. Berdasarkan hasil observasi dan wawancara tersebut diperoleh 5 kriteria diantaranya Pendapatan Orang Tua (K1) diperoleh dari pendapatan perbulan, Jumlah Tanggungan (K2) diperoleh dari banyaknya tanggungan dalam keluarga, Status Tempat Tinggal (K3) diperoleh dari Status Kepemilikan Tempat Tinggal, Prestasi Sekolah(K4) diperoleh dari Peringkat Rangking disekolah, Prestasi di luar Sekolah (K5) diperoleh dari Prestasi diluar sekolah. Sedangkan data sekunder diperoleh melalui tulisan ilmiah dan studi literatur yang penulis lakukan berdasarkan tema penulisan. Hasil dari penelitian ini menghasilkan output yang memenuhi tujuan dan mempermudah proses dalam menentukan siswa yang berhak menerima beasiswa, sehingga menjadi lebih akurat, efektif dan efisien dalam menghasilkan informasi yang dapat digunakan sebagai pendukung keputusan.Kata kunci: Sistem Pendukung Keputusan, Beasiswa, Metode TOPSIS.